2019
DOI: 10.1016/j.yjmcc.2019.01.029
|View full text |Cite
|
Sign up to set email alerts
|

PKC and PKN in heart disease

Abstract: The protein kinase C (PKC) and closely related protein kinase N (PKN) families of serine/threonine protein kinases play crucial cellular roles. Both kinases belong to the AGC subfamily of protein kinases that also include the cAMP dependent protein kinase (PKA), protein kinase B (PKB/AKT), protein kinase G (PKG) and the ribosomal protein S6 kinase (S6K). Involvement of PKC family members in heart disease has been well documented over the years, as their activity and levels are mis-regulated in several patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 219 publications
(279 reference statements)
1
34
0
Order By: Relevance
“…PKCα, β, ε, θ, and δ isoforms have been proposed to be involved in the development of diabetic cardiac hypertrophy (5,33,34). PKCα is the predominant member among the different PKC isozymes expressed in the cardiac tissue (35)(36)(37)(38). PKCα is increased in human cardiac pathology (36,39) and during the transition to heart failure (40).…”
Section: Discussionmentioning
confidence: 99%
“…PKCα, β, ε, θ, and δ isoforms have been proposed to be involved in the development of diabetic cardiac hypertrophy (5,33,34). PKCα is the predominant member among the different PKC isozymes expressed in the cardiac tissue (35)(36)(37)(38). PKCα is increased in human cardiac pathology (36,39) and during the transition to heart failure (40).…”
Section: Discussionmentioning
confidence: 99%
“…Protein kinase C‐related kinase 1 (PRK1; also known as PKN or PAK1) is a trypsin or lipid activated kinase that acts as an effector downstream of RhoA or Rac1, the small GTP‐binding proteins that regulate the assembly of focal adhesion and actin stress fibers, in vivo . Other studies demonstrated that PRK1 was required for the survival of cardiac myocytes and guanosine‐mediated protection of neurons under stressed conditions .…”
Section: Introductionmentioning
confidence: 99%
“…Protein kinase C is a family of ubiquitous serine/threonine kinases subdivided into three groups, according to their biochemical properties: (1) conventional (or classic) PKCs (α, βI, βII, and γ), which are Ca 2+ -and lipid-dependent; (2) novel PKCs (δ, θ, ε, and η), which are Ca 2+ -independent; and (3) atypical PKCs (ζ, ι/λ), which are Ca 2+ -independent but activated by lipids (recently review by [21]). All these isozymes are expressed in cardiac cells including cardiomyocytes, fibroblasts, and mast cells [29].…”
Section: Pkcs As Intracellular Nodes In Heart Failure Pathophysiologymentioning
confidence: 99%
“…Protein kinase is a class of enzymes that modify other proteins by chemically adding the terminal γ-phosphate group of adenosine triphosphate (ATP) to serine, threonine, or tyrosine residues, also known as phosphorylation [21]. Special attention has been given to the relationship between the protein kinase C (PKC) and cardiac dysfunction, including heart failure [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation